Counseling on The Use of Nesting For Low Birth Weight (LBW) Babies in The Perinatology Room of Banten Province Hospital (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Introduction Birth weight is the weight of a baby one hour after birth. Normal birth weight is between 2500-4000 grams , while babies with birth weight